Peningkatan Kesadaran Hidup Sehat melalui Pembelajaran Gaya Hidup Sehat pada Siswa Kelas 2 SDN Sumur Welut 1/438 - Wahyuningtyas, Anik Tri; Hidayat, Ari Nur; Mohsin, Asfat; Putra, Bagoes Oktaf Syach; Susetyo, Bagus Lukvi; Muhammad; Sulistyawan, Danang (MAN Insan Cendekia Jambi, 2025)
Instilling an early awareness of the significance of having a healthy lifestyle is crucial, particularly at the primary school level. When students learn about healthy lifestyles in an effective way, they are more likely to adopt these practices over time. The purpose of this research is to examine how well second graders at SDN Sumur Welut 1/438 Surabaya grasp the concept of healthy lifestyles after participating in a learning program focused on this topic. Two learning cycles combining observation, interviews, and recording were used in this research using the Classroom Action Research (CAR) technique. The research included 29 second-graders from SDN Sumur Welut 1/438 in Surabaya. The findings demonstrated that the pupils' comprehension of healthy lifestyles improved. While in the Pre-Cycle level, most pupils remained in the